220 likes | 473 Views
Function Composition. Function Composition. Fancy way of denoting and performing SUBSTITUTION But first ….let’s review. Function notation: f(x) This is read “f of x”. This DOES NOT MEAN MULITPLY f and x. Finding the Value of a Function. If f(x) = 3x - 1, find f(2).
E N D
Function Composition • Fancy way of denoting and performing SUBSTITUTION • But first ….let’s review.
Function notation: f(x) This is read “f of x”. • This DOES NOT MEAN MULITPLY f and x.
Finding the Value of a Function If f(x) = 3x - 1, find f(2). • Substitute 2 for x and simplify. • f(2) = 3(2) – 1 = 6 - 1 = 5
Finding the Value of a Function Given g(x) = x2 - x, find g(-3) g(-3) = (-3)2 - (-3) = 9 - -3 = 9 + 3 = 12 g(-3) = 12 Substitute -3 in for each x then simplify.
Finding the Value of a Function • Given g(x) = 3x - 4x2 + 2, find g(5) g(5) = 3(5) - 4(5)2 + 2 = 15 - 4(25) + 2 = 15 - 100 + 2 = -83 • g(5) = -83 Put 5 in place of every x. Simplify.
Find the Value of a Function • Given f(x) = x - 5, find f(a+1) f(a + 1) = (a + 1) - 5 = a+1 - 5 • f(a + 1) = a - 4
Function Composition • Notation: [fog](x) or f(g(x)) means “f of g of x”. [g0f](x) or g(f(x)) means “g of f of x” The notation in orange is typically used.
Find the Value of a Composition of Functions • Given f(x) = 2x + 5 and g(x) = 8 + x, find f(g(-5)). • First find g(-5)…… g(-5) = 8 + -5 = 3. • Now put 3 in place of g(-5) (Plug 3 into the f function) • f(g(-5)) = f(3) = 2(3) + 5 = 6 + 5 = 11
Find the Value of a Composition of Functions • Given f(x) = 2x + 5 and g(x) = 8 + x, find g(f(-5)). (Note how this problem is different from the problem on the previous slide.) • First find f(-5) by plugging -5 in for x in the f function. f(-5) = 2(-5) + 5 = -10 + 5 = 5 • Now find g(f(-5)) by plugging 5 in for x in the g function. g(5) = 8 + 5 = 13. • g(f(-5)) = 13
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. • f(g(3)) • g(f(3)) • f(g(0)) • g(f(0)) • g(g(3))
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. Find f(g(3)) First find g(3). Remember this means find y when x = 3 for the g function. When x = 3 y = -1
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. • f(g(3)) • First find g(3). Remember this means find y when x = 3. When x = 3 y = -1 Now find f(-1). What is y when x = -1 for the f-function? When x = -1 y = -5 So, f(g(3)) = -1
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. Find: g(f(3)) First find f(3). What is y when x = 3 on the f function? f(3) = 3
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. Find: g(f(3)) First find f(3). What is y when x = 3 on the f function? f(3) = 3 Now find g(3). What is y when x = 3 on the g-function? g(3) = -1 So g(f(3)) = -1
Use the graphs of y = f(x) and y = g(x) to find each of the following compositions. Find: f(g(0)) f(g(0)) = f(2) = 4 Find: g(f(0)) g(f(0)) = g(0) = 2 Find: g(g(3)) g(g(3)) = g(-1) = 3
Composition of Functions • Function Composition is just fancy substitution, very similar to what we have been doing with finding the value of a function. • The difference is that instead of plugging in a number we will be plugging in another function.
Composition of Functions • You still replace x with whatever is in the parentheses. • f(g(x)) basically means plug the g function into the f function and simplify. • g(f(x)) basically means plug the f function into the g function and simplify.
Composition of Functions • If f(x) = x2 + x and g(x) = x - 4, find f(g(x)) • Plug the g function (x – 4) into the f function in place of every x and simplify. • f(g(x)) = f(x - 4) = (x - 4)2 + x - 4 = x2 – 8x + 16 +x - 4 = x2 – 7x + 12
Given f(x) = 2x + 2 and g(x) = x + 4, find f(g(x)). f(g(x + 4)) = 2(x +4) +2 = 2x + 8 + 2 = 2x + 10 final answer
If f(x) = x2 + x and g(x) = x – 4 find g(f(x)). This time put the f-function into the g-function in place of x. g(f(x)) =g(x2 + x ) = x2 + x – 4 Final answer.
If f(x) = 2x + 2 and g(x) = x + 4, find g(f(x)). g(f(x)) = 2x +2 +4 = 2x + 6